2020
DOI: 10.1371/journal.pone.0240847
|View full text |Cite
|
Sign up to set email alerts
|

Root- and foliar-applied silicon modifies C: N: P ratio and increases the nutritional efficiency of pre-sprouted sugarcane seedlings under water deficit

Abstract: Water deficit limits the establishment of sugarcane plants from pre-sprouted seedlings (PSS). Silicon (Si) can mitigate such stress, and your supply in plants with the active absorption mechanism is carried out through roots. However, foliar spraying has been practiced to supply Si in PSS production nurseries. Althought it is known that Si via roots can alter C: N: P ratios, nothing has been reported about its supply via foliar spraying, nor whether such changes interfere with structural nutrient use efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 40 publications
(81 reference statements)
5
40
0
Order By: Relevance
“…3 ), suggesting a possible nutrient translocation from the root and stem to this tissue. A similar result was also reported for wheat 5 and sugar cane 35 , where adding Si in the nutrient solution increased P availability in the leaves while Si involvement in the metabolism of C and P was indicated, with subsequent changes in the nutrient stoichiometry and use efficiency. Studies in the literature suggest that Si changes the positive regulation of the expression of transporter genes for P uptake while increasing the exudation rates of organic acids that play a role in improving P uptake and availability 20 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…3 ), suggesting a possible nutrient translocation from the root and stem to this tissue. A similar result was also reported for wheat 5 and sugar cane 35 , where adding Si in the nutrient solution increased P availability in the leaves while Si involvement in the metabolism of C and P was indicated, with subsequent changes in the nutrient stoichiometry and use efficiency. Studies in the literature suggest that Si changes the positive regulation of the expression of transporter genes for P uptake while increasing the exudation rates of organic acids that play a role in improving P uptake and availability 20 .…”
Section: Discussionsupporting
confidence: 85%
“…The energy cost for incorporating Si in structural compounds is less than the inclusion of C in organic compounds, due to the intrinsic permeability of the lipid bilayers 33 , also contributing to better plant growth. The decreasing C levels in different plant organs have not only been confirmed under normal growing conditions but also in plants grown under abiotic stress conditions, such as salinity 12 , 34 and water deficit 35 , which induces greater energy expenditure by the plant and Si can mitigate this consumption, benefiting these plants.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, as N fixation being increased by better P nutrition [ 5 , 390 ] and Si increasing plants’ P nutrition (as shown for grasses, see above), the positive effect of Si on N fixation may be indirectly due to Si increasing plants P nutrition. For sugarcane, no positive effect of Si on P nutrition was found [ 391 ]. In contrast, Xu et al [ 91 ] found no positive effect of Si on N in legumes.…”
Section: Implications For Ecosystem Structure Functioning and Servicesmentioning
confidence: 99%
“…A large study revealed a negative relationship between Si and N/P ratios for wetland and submerged species and a negative relationship between Si and both C/N and C/P ratios for submerged species [ 289 ]. A study of the effect of Si fertilization on sugarcane found an increase in the C/N ratio by Si for different cultivars and a decrease in the C/P ratio for one cultivar [ 391 ]. A study analyzing grass species in China found an increase in C/N ratio with increasing Si and a decrease in both C/P and N/P ratios with increasing Si [ 393 ].…”
Section: Implications For Ecosystem Structure Functioning and Servicesmentioning
confidence: 99%